2012
DOI: 10.1021/jp203734d
|View full text |Cite
|
Sign up to set email alerts
|

Improving Platinum Catalyst Durability with a Doped Graphene Support

Abstract: Improving the durability of a platinum catalyst is an important step in increasing its utility when incorporated as the anode or cathode of a proton-exchange membrane fuel cell. Using density functional theory, the binding energy between a platinum atom and five graphene surfaces, one pure, and four others singly doped with beryllium, boron, nitrogen, and oxygen, was calculated. The oxygen-doped surface showed the highest binding energy and was calculated to be 7 times higher than the undoped surface. Each dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
74
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 51 publications
14
74
1
1
Order By: Relevance
“…The authors in the research [8] proposed that the sites of oxygen defect on RGO sheets boom the activities of Pt to MOR in a similar mechanism which was found in Pt/RuO 2 . Meanwhile, the DFT simulations demonstrate that the bonding energy of Pt on the surface of oxygen-doped graphene is much higher than that on the undoped surface, which suggests the durability of Pt catalyst will be strengthened greatly on oxygen-doped graphene [9]. Some other theoretical studies also imply that the CO tolerance of Pt clusters can be possibly boosted through engineering the interaction between the Pt clusters and the specific defects on the graphene substrate [10,11].…”
Section: Introductionmentioning
confidence: 97%
“…The authors in the research [8] proposed that the sites of oxygen defect on RGO sheets boom the activities of Pt to MOR in a similar mechanism which was found in Pt/RuO 2 . Meanwhile, the DFT simulations demonstrate that the bonding energy of Pt on the surface of oxygen-doped graphene is much higher than that on the undoped surface, which suggests the durability of Pt catalyst will be strengthened greatly on oxygen-doped graphene [9]. Some other theoretical studies also imply that the CO tolerance of Pt clusters can be possibly boosted through engineering the interaction between the Pt clusters and the specific defects on the graphene substrate [10,11].…”
Section: Introductionmentioning
confidence: 97%
“…These authors found that altering the charge of the Pt cluster from negative to positive could tune the CO binding strength from strong to weak. Groves et al 181 probed the ability of dopants to deliver enhanced PtNP stability by reporting adsorption of a single Pt atom on pristine and doped (Be, B, N and O) graphene flake substrates 42 carbons) using real-space B3LYP calculations with modest basis sets. In agreement with previous calculations, B-doping was found to yield greater Pt stability than N-doping.…”
Section: Fuel Cellsmentioning
confidence: 99%
“…Because the binding energy is much related with the structural stability and the catalytic activity [35][36][37], we firstly investigate the binding energy between Pt cluster and WACNTs. In the quench process of each MD simulation (100 ps dynamic time and 0.5 fs time step), we record and save the equilibrium structures every 10,000 steps; as a result, 21 Pt/WACNT structures are obtained, including their velocities, energies, and temperatures.…”
Section: The Largest Binding Energymentioning
confidence: 99%